Transport risks in the supply chains – Post COVID-19 challenges - Chodakowska, Ewa; Bazaras, Darius; Sokolovskij, Edgar; Kuranovic, Veslav; Ustinovichius, Leonas (Journal of Business Economics and Management, 2024)
The COVID-19 pandemic has caused major disruptions in global supply chains with unforeseen and unpredictable consequences. However, the pandemic was not the only reason why supply chain risk management has become more crucial than ever before. In the last decade, the occurrence of previously merely theoretical risks has emphasised the importance of risk management in supply chains. This has increased interest in risk assessment and management, COVID-19 and other disaster impact studies and proposals for more stable and resilient supply chains. This article addresses the problem of transport risk in supply chains in the context of COVID-19. Particular attention is paid to quantitative approaches. Identifying and quantifying risks and modelling their interdependencies contribute to the stability of the supply chains. The analysis presents the current state of knowledge and can serve as a guide for further research. It highlights transport risk management in supply chain management as an important area of investigation. In light of the challenges of the COVID-19 pandemic, the article proposes an approach to transportation risk assessment based on quantitative assessment and interconnection of risk factors.